Preparation and Application of Decellularized ECM-Based Biological Scaffolds for Articular Cartilage Repair: A Review - Zhang, Qian; Hu, Yixin; Long, Xuan; Hu, Lingling; Wu, Yu; Wu, Ji; Shi, Xiaobing; Xie, Runqi; Bi, Yu; Yu, Fangyuan; Li, Pinxue; Yang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Cartilage regeneration is dependent on cellular-extracellular matrix (ECM) interactions. Natural ECM plays a role in mechanical and chemical cell signaling and promotes stem cell recruitment, differentiation and tissue regeneration in the absence of biological additives, including growth factors and peptides. To date, traditional tissue engineering methods by using natural and synthetic materials have not been able to replicate the physiological structure (biochemical composition and biomechanical properties) of natural cartilage. Techniques facilitating the repair and/or regeneration of articular cartilage pose a significant challenge for orthopedic surgeons. Whereas, little progress has been made in this field. In recent years, with advances in medicine, biochemistry and materials science, to meet the regenerative requirements of the heterogeneous and layered structure of native articular cartilage (AC) tissue, a series of tissue engineering scaffolds based on ECM materials have been developed. These scaffolds mimic the versatility of the native ECM in function, composition and dynamic properties and some of which are designed to improve cartilage regeneration. This review systematically investigates the following: the characteristics of cartilage ECM, repair mechanisms, decellularization method, source of ECM, and various ECM-based cartilage repair methods. In addition, the future development of ECM-based biomaterials is hypothesized.